Factors Associated With Work-Related Musculoskeletal Disorders (WMSDs) Among Tofu Industry Workers In Jambi City 2026 - Putri Fara Diba; Rumita Ena Sari; Budi Aswin Sanrus; Puspita Sari; Andree Aulia Rahmat (CV. AFDIFAL MAJU BERKAH, 2026)
Work-related musculoskeletal disorders (WMSDs) are common occupational health complaints among industrial workers who perform manual tasks and maintain non-ergonomic work postures. This study aims to analyze the factors associated with WMSD complaints among soybean curd industrial workers in Jambi City in 2026. A quantitative study design with a cross-sectional approach was used in this study. The study population consisted of 45 workers, all of whom were included in the sample using total sampling. Data collection involved observation using the Rapid Entire Body Assessment (REBA) method, measurement of postural angles using a protractor, and completion of the SNI 9011:2021 questionnaire. Data were analyzed using univariate and bivariate methods, specifically the Chi-Square test with a 95% confidence level. The results showed that 57.8% of workers experienced WMSD complaints associated with high risk. Bivariate analysis revealed a significant association between WMSD complaints and work posture (p=0.001), work duration (p=0.019), repetitive movements (p=0.001), and length of service (p=0.036), whereas age did not show a significant association (p=0.436). It was concluded that work posture, work duration, repetitive movements, and length of service are factors associated with WMSD complaints among tofu industry workers. Improvements in workplace ergonomics, work scheduling, and the implementation of occupational safety and health programs are necessary to reduce the risk of musculoskeletal disorders.